ANALISIS KARAKTERISTIK PERUSAHAAN TERHADAP TINGKAT DISCLOSURE LAPORAN KEUANGAN - Ustman Ustman (Universitas Pakuan, 2020)
The purpose this study is to empirically examine the characteristics of companies on the level of disclosure financial statements. Disclosure financial statements is very important for shareholders and creditors to assess the quality of a company's accounting information. So transparency is needed from management to give trust to stakeholders. There are four characteristics of a company that can affect the level of disclosure of financial statements, namely liquidity, leverage, profitability and firm size. The number of samples used in this study were 43 manufacturing companies listed on the Indonesia Stock Exchange. Data analysis uses multiple linear regression. The results obtained showed that the variables of liquidity, leverage, profitability and firm size do not affect the level of disclosure financial statements. The implication of the research result is that report disclosure is an obligation in every report so it is not appropriate if it is related to company characteristics.